DEVELOPMENT OF CHEMISTRY STUDENT WORKSHEET WITH INDUCTIVE-DEDUCTIVE APPROACHES AS A PREVENTIVE MEANS TO THE MISCONCEPTION ON CHEMICAL BONDING MATERIAL STUDENTS AT SENIOR HIGH SCHOOL GRADE 10th (UNESA Journal of Chemical Education, 2019)
AbstractThe aims of this research are to know the advisability of chemistry student worksheet with inductive-deductive approach as a preventive means to the misconception on chemical bonding material in terms of validity, practicality and effectiveness. This research has been taken place in SMA Negeri 1 Cerme-Gresik on December 2017. Limited trials were conducted to 15 students. This research was conducted done for three meetings. Validity was obtained from the validation of student worksheet by 2 lecturers of chemistry and one chemistry teacher using validity sheet. Practicality was obtained from the result of questionnaire of student response to student worksheet supported by observation data of student’s activity. Effectiveness was obtained from the results of student’s misconception tests after the implementation of limited trials of 15 students. Instruments that used in this research were observation sheet activity, questionnaire, observation sheet student’s responses and misconception test sheet. It can be concluded that (1) the chemistry student worksheet validation result of content criteria, linguistic criteria, presentation criteria, graphic criteria respectively as follows 86.11%; 82.78%; 85.34%; 85.00% in very valid category, (2) The percentage of student responses based on content criteria, linguistic criteria, presentation criteria, graphic criteria respectively as follows 94,00%, 86,67%, 95,55%, 84,44% in very practice category, (3) Misconception test results in chemical bonding materials showed that all students have percentage under 45,00% of very low misconception. Thus, the chemistry student worksheet that has been developed was feasible based on thatthree findings. Chemistry student worksheet with inductive-deductive approach concluded feasible to be used but still need to be done last phase from Thiagarajan development that disseminate. Keywords: Development Research, Inductive-Deductive Approach, Preventive, Misconception, Chemical Bonding